Networks for Grid Applications Second International Conference, GridNets 2008, Beijing, China, October 8-10, 2008, Revised Selected Papers - Vicat-Blanc Primet, Pascale; Kudoh, Tomohiro; Mambretti, Joe.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2009)
This book constitutes the thoroughly refereed post-conference proceedings of the Second International Conference on Networks for Grid Applications, GridNets 2008, held in Beijing, China in October 2008. The 19 revised full papers presented together with 4 invited presentations were carefully reviewed and selected from 37 submissions. The papers address the whole spectrum of grid networks, ranging from formal approaches for grid management to case studies in optical switching.
A High Performance SOAP Engine for Grid Computing -- UDTv4: Improvements in Performance and Usability -- The Measurement and Modeling of a P2P Streaming Video Service -- SCE: Grid Environment for Scientific Computing -- QoS Differentiated Adaptive Scheduled Optical Burst Switching for Grid Networks -- Principles of Service Oriented Operating Systems -- Preliminary Resource Management for Dynamic Parallel Applications in the Grid -- Performance Evaluation of a SLA Negotiation Control Protocol for Grid Networks -- Performance Assessment Architecture for Grid -- Implementation and Evaluation of DSMIPv6 for MIPL -- Grid Management: Data Model Definition for Trouble Ticket Normalization -- Extension of Resource Management in SIP -- Economic Model for Consistency Management of Replicas in Data Grids with OptorSim Simulator -- A Video Broadcast Architecture with Server Placement Programming -- VXDL: Virtual Resources and Interconnection Networks Description Language -- Adding Node Absence Dynamics to Data Replication Strategies for Unreliable Wireless Grid Environments -- Hop Optimization and Relay Node Selection in Multi-hop Wireless Ad-Hoc Networks -- Localization Anomaly Detection in Wireless Sensor Networks for Non-flat Terrains -- Network Coding Opportunities for Wireless Grids Formed by Mobile Devices -- Automatic Network Services Aligned with Grid Application Requirements in CARRIOCAS Project -- Communication Contention Reduction in Joint Scheduling for Optical Grid Computing -- Experimental Demonstration of a Self-organized Architecture for Emerging Grid Computing Applications on OBS Testbed -- Joint Scheduling of Tasks and Communication in WDM Optical Networks for Supporting Grid Computing -- Manycast Service in Optical Burst/Packet Switched (OBS/OPS) Networks (Invited Paper) -- OBS/GMPLS Interworking Network with Scalable Resource Discovery for Global Grid Computing -- Providing QoS for Anycasting over Optical Burst Switched Grid Networks -- A Paradigm for Reconfigurable Processing on Grid.
Keywords: Computer science; Computer organization; Computer communication systems; Computer system failures; Computers; Management information systems; Computer engineering; Computer Science; Computer Communication Networks; Computer Engineering; Theory of Computation; Computer Systems Organization and Communication Networks; Management of Computing and Information Systems; System Performance and Evaluation; Electronic books